Teaching Speaking Skills through Inquiry Technique - Hendriwanto, Hendriwanto (ELT Perspective Jurnal Pendidikan Bahasa Inggris, 2014)
ABSTRACT This study focuses on the teaching speaking skills through inquiry technique. This study was aimed at finding the effectiveness of the use of inquiry technique in improving studentsâ speaking skills. It was done under several ways and by giving pre-test and post-test. The population of the study is the first grade students of English education of Unswagati. The writer took two classes (class GH & CD) for the sample of the study. The study was carried out through experimental research by using the t-account formula. The findings of the study are as follows. The average pre-test and post-test experiment class is 21.83 but in the control class get 13. It is different from the average of the class. The result of taccount3.17, while the critical value of taccount is higher than ttable (3.17taccount> 2.002ttable). This could be seen that t observed is higher than t table and there are differences between Mx and My by the formula application. It shown that the final result of this research stated has a fositive influence.